A 2D Nanoradiosensitizer Enhances Radiotherapy and Delivers STING Agonists to Potentiate Cancer Immunotherapy. Issue 39 (26th August 2022) - Luo, Taokun; Nash, Geoffrey T.; Jiang, Xiaomin; Feng, Xuanyu; Mao, Jianming; Liu, Jianqiao; Juloori, Aditya; Pearson, Alexander T.; Lin, Wenbin
Abstract: Despite potent preclinical antitumor activity, activation of stimulator of interferon genes (STING) has shown modest therapeutic effects in clinical studies. Many STING agonists, including 2′, 3′‐cyclic guanosine monophosphate–adenosine monophosphate (cGAMP), show poor pharmacokinetic properties for sustaining STING activation in tumors and achieving optimal antitumor efficacy. Improved delivery of STING agonists and their effective combination with other treatments are needed to enhance their therapeutic effects. Herein, a 2D nanoplatform, cGAMP/MOL, is reported via conjugating cGAMP to a nanoscale metal–organic layer (MOL) for simultaneous STING activation and radiosensitization. The MOL not only exhibits strong radiosensitization effects for enhanced cancer killing and induction of immunogenic cell death, but also retains cGAMP in tumors for sustained STING activation. Compared to free cGAMP, cGAMP/MOL elicits stronger STING activation and regresses local tumors upon X‐ray irradiation. Further combination with an immune checkpoint inhibitor bridges innate and adaptive immune systems by activating the tumor microenvironment to elicit systemic antitumor responses. Abstract : A 2D metal–organic layer (MOL) functions as a potent nanoradiosensitizer and a nanocarrier for agonists of stimulator of interferon genes (STING) for cancer treatment. STING agonists are conjugated onto an MOL via phosphate linkages, resulting in prolonged tumor retention and enhanced STING activation. Further combination with immune checkpoint blockade extends the scope of this local treatment to elicit systemic antitumor responses.